Some Ethiopian Historical Poems - Molvaer, Reidulf K. (Aethiopica, 2006)
It has been common to compose short poems in relation to various memorable events or situations in the lives of Ethiopian rulers. A very few rulers also composed such poems themselves, TéwodrosII being one of them. The poems in this article cover the reigns from TéwodrosII to Hayle-SillaséI (with one brief omission: the rule of Tekle-Gïyorgïs, 1868–1872). Poems of ridicule and blame are as common as poems of praise. ATTENTION: Due to copy-right no online publication is provided.